2017
DOI: 10.1093/cz/zox053
|View full text |Cite
|
Sign up to set email alerts
|

Does exploratory behavior or activity in a wild mouse explain susceptibility to virus infection?

Abstract: Exploration and activity are often described as trade-offs between the fitness benefits of gathering information and resources, and the potential costs of increasing exposure to predators and parasites. More exploratory individuals are predicted to have higher rates of parasitism, but this relationship has rarely been examined for virus infections in wild populations. Here, we used the multimammate mouse Mastomys natalensis to investigate the relationship between exploration, activity, and infection with Morog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 82 publications
0
25
1
Order By: Relevance
“…Second, we have found evidence for the existence of consistent differences in exploration, (i.e., animal personality) in this species (Vanden Broecke et al, ). Nevertheless, while it has been hypothesized that personality may affect virus infection probability (Barber & Dingemanse, ; Kortet, Hedrick, & Vainikka, ), we found no behavioral differences among individuals with or without MORVab (Vanden Broecke et al, ; Figure (3&4)).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Second, we have found evidence for the existence of consistent differences in exploration, (i.e., animal personality) in this species (Vanden Broecke et al, ). Nevertheless, while it has been hypothesized that personality may affect virus infection probability (Barber & Dingemanse, ; Kortet, Hedrick, & Vainikka, ), we found no behavioral differences among individuals with or without MORVab (Vanden Broecke et al, ; Figure (3&4)).…”
Section: Introductionmentioning
confidence: 75%
“…Activity was measured by dividing the floor of the box into 12 squares and counting the number of times an individual changed squares during 10 min (Vanden Broecke et al, ). This was quantified using MTrackJ (Meijering, Dzyubachyk, & Smal, ), a plugin for ImageJ (Schneider, Rasband, & Eliceiri, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, a positive relationship was found between behaviour in a novel environment and activity in a familiar environment (David, Auclair, & Cézilly, ; Siwak, Murphey, Muggenburg, & Milgram, ), as well as the former and risk‐taking behaviour (David et al, ; van Oers, Drent, Goede, & Noordwijk, ), indicating that behaviour in novel environment is connected to activity and risk‐taking behaviour in other contexts. However, not every study found such relationships (Nyqvist, Gozlan, Cucherousset, & Britton, ; Ruuskanen & Laaksonen, ; Vanden Broecke et al, ). Behaviour in novel environment is apparently also related to the stress response, as slow exploring birds generally had higher stress responses (Baugh et al, ; Bousquet, Petit, Arrivé, Robin, & Sueur, ; Carere, Groothuis, Mostl, Daan, & Koolhaas, ), but an opposite relationship was found in rodents (Crino, Larkin, & Phelps, ).…”
Section: Introductionmentioning
confidence: 99%